First report of Curvularia lunata associated with stem disease of cassava - Msikita, W.; Yaninek, John S.; Ahounou, M.; Baimey, H.; Fagbemissi, R. (Scientific Societies, 1997)
During surveys covering 60 cassava (Manihot esculenta Crantz) fields, randomly selected (between latitude 4°55′N and 8°16′N) in south Ghana, and 27 fields in southeast (between 4°50′N and 7°56′N) Nigeria, 8-month-old or older stems of some cassava genotypes were found to be covered by grayish brown lesions, predominantly on lignified portions of stems. Field disease incidence ranged from 0 to 80%, and severity from no disease to highly affected (>15 lesions per stem). To identify the pathogen, infected stem portions were cut out, surface disinfected, and cultured on potato dextrose agar (PDA) acidified with 0.4% (vol/vol) lactic acid. After 1 week, mycelia, conidiophores, and conidia were observed under a microscope, and the pathogen was identified as Curvularia lunata(Wakk.) Boedijn (confirmed also by the International My-cological Institute, Surrey, U.K.). To complete Koch's postulates, stem pieces of four cassava cultivars (Agric, Tchukunochi, TMS 30572, and Ben 86052), were disinfected in hot water (52°C for 5 min), transplanted in sterilized sand, and maintained in a greenhouse under natural light at 28 to 30°C. Before planting, five stems were wound inoculated (sliced with an epidermal scalpel) just above nodes, and a 5-mm-diameter PDA mycelial plug of C. lunata was applied to each wound or directly to unwounded nodes. Stems were then kept in a plastic bag for 24 h before planting. For each cultivar, five control stem pieces were similarly wounded but not treated with PDA plugs. All plants were maintained under >90% relative humidity. Control plants remained symptom-free whereas lesions and bud necrosis similar to field symptoms were observed on all inoculated plants within 1 month. Symptom development was quicker (2 to 3 weeks) on wound-inoculated than on nonwounded stems. Mortality of artificially wound-inoculated buds ranged between 30 and 100%, depending on genotype and manner of inoculation. Artificially infected stem and bud portions plated on PDA consistently yielded C. lunata. Bud sprouting of naturally infected cuttings was monitored over a period of 4 weeks after stem planting. When buds were completely colonized, sprouting was completely inhibited. However, partially colonized buds sprouted, but growth was reduced by 20 to 50% (depending on genotype), compared with healthy stems. This is the first report of C. lunata pathogenic on cassava.